Brechas entre la formulación y la gestión de la política pública para la recuperación temprana: caso terremoto 16 A. - Cajas Maldonado, Diana Estefanía (2019)
On April 16, 2016, Ecuador was shaken by an earthquake measuring 7.8 on the Richter scale, significantly affecting the province of Manabí (hereinafter Earthquake 16A). During the three following months, the articulation of roles and responsibilities on the part of the Secretaría de Gestión de Riesgos (SGR) both for the decision making of the central level and for the participation of other actors becomes essential, due to social, economic and structural vulnerability generated after the telluric event. This document analyzes the gap between the formulation and management of public policy for early recovery, considering the different ways of understanding the disaster, co-responsibility, organizational structures and inter-institutional coordination of them, allowing to synthesize the effectiveness of government actions, divergences and identify the adjustment needs of the current policy.